FENOMENA UMKM BERBAGI “JUMAT BERKAH” DI YOGYAKARTA - Ari Dyah Sinta; Shulhan; Lessy, Zulkipli (Kodifikasia, 2024)
Nowadays, philanthropy is present in every aspect of society. The absence of the state or the empty role of the state in society has led to an attitude of self-protection that gives rise to all practices of assurance through assistance. The existence of a religious narrative within oneself and the desire to prosper in the community are the main reasons why they want to help. Then, the assistance is institutionalized; there is distrust in managing the assistance, so some givers directly assist, such as what is done by MSME owners who carry out the "Friday Blessing" action. The following will be discussed in this journal paper. This research uses a literature review by applying the theory and perspective of Bourdieu's Sociology of social capital theory to analyze and read the "Friday Blessing" phenomenon. This literature review examines the objectives of MSMEs who carry out alms in "Friday Blessing" in addition to worship and a strategy to attract buyers. One of the results of this study is that MSME actors practice Blessing Friday, not just as a charity but also as a marketing method to get buyers.